Association of ALDH1A1-NEK-2 axis in cisplatin resistance in ovarian cancer cells. Issue 11 (November 2020) - Uddin, Md. Hafiz; Kim, Boyun; Cho, Untack; Azmi, Asfar S.; Song, Yong Sang
Abstract: Development of acquired resistance to cisplatin (CDDP) is a major obstacle in the treatment of ovarian cancer patients. According to the cancer stem cell (CSC) hypothesis, the recurrence and chemoresistance are presumed to be linked to cancer stem/progenitor cells. Here, we investigated the CSC-like phenotypes and mechanism of chemoresistance in CDDP resistant ovarian cancer cells. A well-established CDDP sensitive ovarian cancer cell line A2780 and its resistant population A2780-Cp were used. We also developed a supra resistant population (SKOV3-Cp) from a naturally CDDP resistant cell line SKOV3. Both resistant/supra resistant cell lines showed significantly higher self-renewal capability than their parental counterparts. They also showed significant resistance to apoptosis and sub-G1 arrest by CDDP treatment. Stem cell marker ALDH1 positivity rates were higher both in A2780-Cp and SKOV3-Cp cell lines than in their counterparts, quantified by Aldefluor assay kit. Hoechst 33342 dye effluxing side populations were increased up to about five folds in A2780-Cp cells and two folds in SKOV3-Cp cells compared to A2780 and SKOV3 cells, respectively. Among major stemness related genes ( POU5F1 / OCT4, SOX2, NANOG, NES, BMI1, KLF4 and ALDH1A1 ), ALDH1A1 and KLF4 were significantly overexpressed in both resistant/supra resistant cells. Silencing ALDH1A1 in A2780 and A2780-Cp cells using siRNA greatly reduced the stem cell population and sensitized cells to CDDP. Moreover, silencing of ALDH1A1 reduced the transcript and protein level of its downstream target NEK-2. We also observed the downregulation of ABC transporters (ABCB1/MDR1, ABCG2 and ABCC1/MRP1) either by ALDH1A1 or NEK-2 silencing and upreguation of ABCB1/MDR1 due to the overexpression of NEK-2 . Taken together, the present study suggests that stemness gene ALDH1A1 can be involved in CDDP resistance through the upregulation of NEK-2 in ovarian cancer. Abstract : Cell biology; Cell culture; Cell death; Molecular biology; Cancer research; Cisplatin resistance; Ovarian cancer; ALDH1A1; NEK-2; ABC transporters; Stemness.